Transitioning From Room to Zoom: The 2020 Cardiovascular Fellows’ Boot Camp in the COVID-19 Era - Akanksha Thakkar; Yehia Saleh; C. Huie Lin; William Zoghbi; Nadeen Faza; Bindu Chebrolu (Methodist DeBakey Cardiovascular Journal)
For 10 years, the annual Houston Methodist Cardiovascular Fellows’ Boot Camp hosted hundreds of cardiovascular trainees in Houston for a concise yet comprehensive 3-day training program for new fellows. The cornerstone of the program was the hands-on Skills Academy, which included a variety of timed learning stations that taught surgical techniques, dissection skills, and suturing techniques as well as echocardiography and cardiac catheterization using simulators. This was followed by 2 days of didactics covering essential topics in each specialty. However, that model was upended in 2020 by the COVID-19 pandemic. The pandemic forced the digitization of medical education and posed significant challenges as we transitioned Boot Camp to a virtual format. In this editorial, we review our experience designing and implementing a virtual cardiology track of the Houston Methodist Cardiovascular Fellows’ Boot Camp and highlight challenges and proposed solutions in the era of virtual education.